Protection of freshwater resources from environmental degradation caused by acid mine drainage : a critical comparative analysis between the South African and German legal frameworks and judicial remedies - Louw, Marianca (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLD)--Stellenbosch University, 2020.